The Analysis of Batata Sentence of Ciacia Language in Traditional Medicine (e-Journal of Linguistics, 2023)
Batata is one of the aspect of mantras lyrical that lexically can beunderstood and its contextual meaning based on the necessity. Batatasentence in traditional medicine has not been conducted yet. It is theone of various linguistic aspects. The study present deals with thesentence analysis of batata in traditional medicine of Ciacialanguage. It has main objectives is formulating and analyzing typesof sentences batata in Ciacia language. This is a kind of descriptive-qualitative research which employs a distributional method in dataanalysis with the underlying theories of syntax. The data taken frominforman directly when he has been acted patient treatment for theseveral times. The result of this study, it found that sentence of batatais filled by Imperative sentences filled by the swear marker consistsof pindongo ‘hear’ + S + P + O and compound sentences consist oftwo clause and four clause. It can be formulated syntactically [if + S+ P + Pel] as first clause, while [S + P] as second clause, and [if +P- (no) as first clause, while [S + P] [S + P] [S + P] as second,third, fourth clause.
Keywords: Batata; Sentence Analysis; imperative; compound sentences